Effect of Self -Efficacy and Distributive Justice on Employees’ Performance in Federal Capital Territory Area Councils, Abuja - Yahaya, Garba Shekwonuchie; Innocent, Idachaba Odekina; Tomi, Saliu Hakeem (International Journal of Small and Medium Enterprises, 2020)
The well-being of every organization and institution lies on the performance of its employees. Local government area councils are created to render services and to address the social needs of the people. These services are highly essential to the sustenance of people at this level. However, when workers who are employed to discharge all these services on behalf of the government to the people are unable to perform their jobs as expected, problems arises as the expected social and economic service are barely executed. The study aimed at examining the effect of self-efficacy and distributive justice on employees’ performance in FCT area councils, Abuja. A survey research design was used and primary data were gathered through the use of questionnaire. A total of 217 returned questionnaires were analyzed. Structural equation model was used to analyze data using Smartpls2. Findings reveal that distributive justice and self-efficacy have a positive and significant effect on employees’ performance. The study, therefore, recommends that the operation of distribution justice should be encourage at the grass root level since the employees are motivated by their reward at the end of the day; Self efficacy of the employees’ should also be improve through effective initiatives so as to motivate employees to perform their jobs optimally.